Influência do Oncideres impluviata (Germar, 1824) na produtividade de Acacia mearnsii (De Wild) no Rio Grande do Sul, Brasil - Badin, Tiago Luis (2023)
This work aims to evaluate the influence on productivity caused by Oncideres impluviata in Acacia mearnsii. For the evaluation, data from four black wattle management units in the municipality of Encruzilhada do Sul, RS, were used. The data obtained, via forest inventory, were used to calculate the total volume and commercial volume obtained by the non-linearized Spurr and non-linearized Schumacher-Hall models, the volumetric distributions of the data year by year were also tested and submitted to the Kruskal test - Wallis. The results obtained showed that trees attacked on lateral branches have the same volume as non-attacked trees, however, they differ only in terms of the type of attack, if this is on the apical bud, which occurs at two years old, has long-term alteration in commercial volume, accumulating losses directly attributed to the insect ranging from 48.42% to 83.5% depending on the level of attack. It was concluded that the insect is indeed one of the causes of volume reduction, especially when the apical attack occurs at two years of age.